Effects of pH on the Shape of Alginate Particles and Its Release Behavior - Lin, Yung-Sheng; Huang, Wen-Ying; Hsu, Tzu-Fang; Lo, Szu-Hsuan; Huang, Yu-Ya; Chuang, Jui-Jung; Huang, Shu-Ling (International Journal of Polymer Science, 2017)
A vast majority of alginate particles exist as spheres in most practical uses, and both the particle shape and size are the key factors dominating the applications and performance of alginate gels. Therefore, it becomes an issue of great interest to investigate the aspheric alginate particles. As the first step, various shaped alginate particles were formed due to various pH values in gelation solutions. It was experimentally demonstrated that a low pH brought about an oblate shape, and particularly lower concentrations of both alginate and divalent cations resulted in a flattened oblate shape. Ba2+ acting as a cross-linker had a less impact on the particle shape than Ca2+ due to a higher affinity in alginate intermolecular cross-linking. With a larger surface area, an oblate particle offered a higher release rate than a spheric one.